Evaluation of MVNO model implementation in remote and border areas using the consistent fuzzy preference relations method - Anggun Fitrian Isnawati; Ridwan Pandiya; Ade Wahyudin (JURNAL INFOTEL, 2021)
Law No. 36 of 1999 concerning Telecommunication has brought many changes, especially in the development of telecommunications infrastructure in Indonesia. However, the penetration of telecommunications services in the forefront, outermost, and backward regions is still relatively low. The government has made various efforts in terms of minimizing the gap in telecommunication services between urban and rural areas through various programs. However, an acceleration is needed so that the service disparity can be immediately overcome. One of the telecommunications products that can be applied to overcome these barriers is the Mobile Virtual Network Operator (MVNO). This study evaluates the most appropriate type of MVNO model to be applied in Indonesia by implementing the Consistent Fuzzy Preference Relations (CFPR) method. This method is able to accommodate expert opinion through a series of scientific steps so as to produce weights for each alternative type of MVNO model. The results obtained are that the most appropriate model to be applied in Indonesia by taking into account the criteria given. The implementation of this model is expected to be able to encourage the optimization of BTS USO that has been declared by the government.